Evaluation of transgenic lines of field pepperweed (Lepidium campestre L.) - Holst, Rikard (SLU/Dept. of Plant Breeding (from 130101), 2013)
The worldwide industrial demand of energy, often in form of fossil fuel, is continuously growing and at the same time these resources are coming to an end (Hamamre, 2013). The interest and focus in renewable sources are then more important than ever and plants are suggested to be a good alternative for production of raw material for industrial purposes (Nilsson et al., 1998). But the world is also facing an increasing world population which also increase the nutritional needs, plants therefore need to be suitable for both industrial and nutritional purposes. To achieve this, common plants need to be improved but it also need new potential crops to be developed and introduced (Carlsson et al., 2009). Modern technology like gene engineering is an important tool to achieve these challenges (Carlsson et al., 2011).